2005
DOI: 10.1016/j.nuclphysa.2005.05.158
|View full text |Cite
|
Sign up to set email alerts
|

The C-odd four-gluon state in the color glass condensate

Abstract: The study of the perturbative Odderon at high gluon densities in the color glass condensate requires to take into account states with more than three gluons. We formulate evolution equations for these states in which the number of gluons is not fixed during the evolution. We further determine the coupling of these Odderon states to the γ → η c impact factor for arbitrary numbers of gluons. We find an exact solution of the evolution equation for the four-gluon Odderon state in terms of the three-gluon Odderon s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 50 publications
2
11
0
Order By: Relevance
“…In particular, it should also extend into the perturbative region of large Q 2 or large √ −t. In this context it is worth pointing out that the result matches nicely the perturbative result of [31] where the diffractive reaction γ ( * ) p → η c p was considered at high energies. In that reaction perturbation theory can be applied because of the large scale given by the charm quark mass.…”
Section: Results and Conclusionsupporting
confidence: 79%
See 1 more Smart Citation
“…In particular, it should also extend into the perturbative region of large Q 2 or large √ −t. In this context it is worth pointing out that the result matches nicely the perturbative result of [31] where the diffractive reaction γ ( * ) p → η c p was considered at high energies. In that reaction perturbation theory can be applied because of the large scale given by the charm quark mass.…”
Section: Results and Conclusionsupporting
confidence: 79%
“…In leading order in perturbation theory only diagrams of type (a) contribute to the γ ( * ) → η c impact factor. In [31] this impact factor was computed for an arbitrary number of gluons exchanged in the t-channel. It was found that for any number of exchanged gluons the impact factor, and hence the amplitude for that reaction, is linear in the quark mass.…”
Section: Results and Conclusionmentioning
confidence: 99%
“…In QCD, where the corresponding generators are in the fundamental representation, the analog of the above combination of traces (3.35) is in general non-zero. In particular, the n t-gluons form in the Regge-limit a bound state for which the EGLLA was formulated in [41]. However, if the generators in the trace (3.35) are in the adjoint representation, we find…”
Section: Decoupling Of the Odderonmentioning
confidence: 96%
“…In order to obtain Odderon exchanges in the t-channel we have to consider impact factors that describe the transition from a C-odd to a C-even state, for example from an R-current as considered above to a pseudoscalar current. As explained in detail in [41] for the case of Dirac fermions, the fermionic loop in such an impact factor with n gluons attached gives rise to the color factor tr (T a 1 . .…”
Section: Decoupling Of the Odderonmentioning
confidence: 99%
See 1 more Smart Citation